Biotransfomation products from Clarius batrachus oil - Omar, Muhammad Nor; Shaban, Norhayati; Bakar, Latifah Munirah; Zuberdi, Ahmad Muzammil; Yunus, Kamaruzzaman (2011)
Biotransformation can be defined as an application that utilized natural and recombinant organisms’ enzymes secreted by yeast, fungi and bacteria or whole cells as catalyst in synthesis of organic compound. Therefore, Pseudomonas aeruginosa bacterium has been chosen to be the biocatalyst for biotransformation of ω fatty acids extracted from Malaysian catfish, Clarias batrachus emphasizing on bioconversion of arachidonic acid. In addition, arachidonic acid was one of prostaglandin precursor which exerts a variety of pharmacological effects on human and animals. In this study, the fatty acids were extracted from the catfish using modified Folch method where the fish flesh was freeze dried prior to homogenization with the chloroform and methanol system. Then, the crude lipid extract was added to the bacterial culture and incubated for 4 days. After incubation, the biotransformation product was extracted and analyzed by using gas chromatography and mass spectrometer (GC-MS) to identify the fatty acids and other compounds. It was found that several fatty acids, especially ω-fatty acids were converted to cholesterol. This indicates that ω-fatty acids can be used as starting materials for other bioactive metabolites for pharmaceutical purposes.